2021
DOI: 10.1038/s41467-021-23733-5
|View full text |Cite
|
Sign up to set email alerts
|

Insights into household transmission of SARS-CoV-2 from a population-based serological survey

Abstract: Understanding the risk of infection from household- and community-exposures and the transmissibility of asymptomatic infections is critical to SARS-CoV-2 control. Limited previous evidence is based primarily on virologic testing, which disproportionately misses mild and asymptomatic infections. Serologic measures are more likely to capture all previously infected individuals. We apply household transmission models to data from a cross-sectional, household-based population serosurvey of 4,534 people ≥5 years fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 29 publications
15
65
1
Order By: Relevance
“…Probably due to the intense social mixing of young and old in the camp, the 50+ age group was one of the most exposed, which is worrying as they are at greatest risk of mortality. The survey also shows that having an infected person in the household is another factor that more than doubles the risk of infection; which is consistent with the results of other studies [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…Probably due to the intense social mixing of young and old in the camp, the 50+ age group was one of the most exposed, which is worrying as they are at greatest risk of mortality. The survey also shows that having an infected person in the household is another factor that more than doubles the risk of infection; which is consistent with the results of other studies [ 10 ].…”
Section: Discussionsupporting
confidence: 91%
“…All the results obtained in the present study strongly suggest that males are not only more susceptible to COVID-19 severity, as shown in worldwide epidemiological surveys, but they are also more likely to transmit the virus to their partners when compared to females in the household transmission context. The epidemiological findings in the present survey are consistent with the results of other published studies involving couples where one of the partners was infected by their spouses [ 40 , 41 ]. Female individuals aged between 17 and 65 years were also frequently found to be secondary cases [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Apparent asymptomatic transmission is often re-classified as pre-symptomatic transmission, i.e., transmission that occurs in the days before symptom onset [24][25][26] . The household secondary attack rate for truly asymptomatic index cases has been found to be lower than for symptomatic index cases 24,[26][27][28][29][30] . A systematic review of 45 studies found that the secondary attack rate for asymptomatic index cases was 60% lower than for symptomatic index cases 29 .…”
Section: Methodsmentioning
confidence: 91%
“…A systematic review of 45 studies found that the secondary attack rate for asymptomatic index cases was 60% lower than for symptomatic index cases 29 . A different analysis of serological data from Switzerland found that asymptomatic cases had a 70% lower odds (34-88%) of infecting another household member compared to cases with symptoms 30 . Another modelling study of contact tracing estimated that transmission due to truly asymptomatic cases was limited, with pre-symptomatic and symptomatic transmission contributing the remainder in approximately equal proportions 31 .…”
Section: Methodsmentioning
confidence: 96%